Analysis of Efficiency and Dominant Factors of Tourism Budget Allocation on Tourism Development in Kampar Regency: Integration of Mixed Methods Analysis - Zamhur, Zamhur; Marantika, Abshor (Dinasti Publisher, 2026)
This study analyzes the efficiency of local government budget (APBD) allocation in the tourism sector of Kampar Regency. The background indicates that despite the significant potential of tourism to boost local revenue, budget allocation and absorption remain suboptimal, with a large portion consumed by operational activities and official travel. The research aims to analyze the dominant factors influencing budget allocation efficiency and evaluate its impact on tourism development in Kampar Regency. Employing a mixed-methods approach (quantitative and qualitative) with descriptive design, Data Envelopment Analysis (DEA and Budget Ratio) and Multiple Linear Regression analysis, the findings reveal that wasteful spending and inadequate efficiency measurement indicators are key weaknesses requiring immediate attention. Although efficiency strategies and stakeholder participation are strong, structural inefficiencies in operational expenditures hinder performance improvement. In conclusion, optimizing the tourism budget in Kampar Regency necessitates a focus on reducing waste and developing measurable performance indicators.